(untitled) (Zamonaviy ilmiy-texnik tadqiqotlar, 2026)
This article explores the necessity of developing the physical and functional preparedness of skilled handball players. It highlights the importance of improving endurance, strength, agility, and coordination to enhance athletic performance. The study also examines the physiological aspects that influence handball players’ efficiency, emphasizing training methodologies that optimize their overall fitness. By analyzing modern approaches and scientific research, the article provides insights into effective training strategies to ensure the sustainable development of handball players’ physical and functional capabilities.